Historical Analysis of Flood Disaster in Trenggalek 2006-2022 - Lailatul Fitriyah; Rohmah, Ani Zulfatul (Universitas Negeri Semarang, 2025)
Flooding is a phenomenon that often occurs in Indonesia. Floods have a significant impact on people's lives. Flood events that often occur in various regions lead the author to examine more deeply related to flood events and forms of disaster mitigation, especially in the Trenggalek area. In the process, the purpose of this research is to historically analyse flood disasters in Trenggalek in 2006-2022. The method in this research uses historical research methods using five steps, namely topic selection, heuristics, source criticism, interpretation and historiography. The results prove that Trenggalek is one of the areas where flooding often occurs every year. The floods are caused by several factors that have a huge impact on people's lives, both material and immaterial losses in the form of casualties, property and can even paralyse the socio-economic activities of the community. This study shows related flood events from 2006 to 2022 that occurred in Trenggalek and the efforts made by the government and the community as a form of disaster mitigation that is more systematic as flood management.